Package Information Used by Older Adults to Identify Whole Grain Foods. Issue 2 (2nd April 2016) - Violette, Catherine; Kantor, Mark A.; Ferguson, Katharine; Reicks, Marla; Marquart, Len; Laus, Mary Jane; Cohen, Nancy
ABSTRACT: A structured interview protocol was used to investigate the ability of older adults (n = 89, age ≥ 65 years) to accurately determine whether three common food items were whole grain, and to assess the package information used in their decision process. Cereal and crackers, which were both whole grain products, were correctly identified by 63% and 66% of participants, respectively. Bread (a refined product), was correctly identified by only 19% of participants, while 46% of participants misidentified the bread as being whole grain. The ingredient list was the information most frequently cited in deciding if a food was whole grain, but participants varied in their ability to accurately interpret it. Package information considered nonpertinent (e.g., the Nutrition Facts label) in identifying a whole grain product was used almost as often as the ingredient list. Older adults would benefit from whole grain education programs that focus on accurately interpreting package information.